Filter-based fingerprint feature extraction - Amnani, Ali (2009)
In the modem world, biometric has become more important in secure way. Modem applications like online banking or online shopping use techniques that depend on personal identification numbers, keys or passwords. Nevertheless, these technologies imply risk of data being forgotten, lost or even stolen. A secure and confidential biometric authentication method is the utilization of fingerprints. Fingerprint were one of the first biometric to be widely use. The lines that flow in various patterns across fingerprint are called ridges and the spaces between ridges are valleys. As the person ages, the fingers do get larger. However ridges stay the same. Usually a technique called minutiae features extraction is used in extracting the fingerprint features to be able to handle automatic fingerprint recognition with computer system. This project proposes a different fingerprint features extraction technique, which uses the features extraction of Gabor filter-based method. There are two important parts in this project which are image pre-processing and feature extraction. The Gabor filter will be used in the image pre-processing process. A system that able to extract the fingerprint features will be built in this project using MATLAB software.